Features of the aerobic energy supply system as a result of the activity of the cardiorespiratory system - Vanyushin, Yu. S.; Elistratov, D. E.; Fedorov, N. A.; Rakhimov, M. I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the features of the aerobic energy supply system as a result of the activity of the cardiorespiratory system, depending on the age of athletes involved in cyclic sports, during bicycle ergometric testing.